RACISM IN JOHN AGARD'S SELECTED POEMS - Gilang Ardinata Prayoga (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2025)
Abstract: Racism has historically shaped social hierarchies that privilege whiteness and marginalize Black identities, embedding inequality into language, education, and cultural institutions. This study explores how is systemic racism presented in John Agard's Selected Poems and what is the significance of systemic racism is in selected poems by John Agard. This study applies qualitative research using Michael Riffaterre’s semiotic of poetry to analyze systemic racism in three of John Agard’s selected poems, “Listen Mr Oxford Don,” “Half-Caste,” and “Checking Out Me History.” Through heuristic and hermeneutic readings, the research identifies ungrammaticalities and reconstructs hypograms to uncover deeper layers of meaning. The findings reveal that Agard’s poetry criticize systemic racism by exposing the marginalization of Black identity, the manipulation of language, and the enduring legacy of colonialism. These semiotic structures convey themes of resistance, cultural pride, and historical reclamation. Ultimately, the study highlights how poetry functions as a powerful medium for resisting systemic oppression and reclaiming identity.Keyword: Systemic Racism, John Agard, Poems, semiotic of poetry